A novel active volumetric rotating disks solar receiver for concentrated solar power generation. (April 2022) - Rández, X.; Zaversky, F.; Astrain, D.
Highlights: The complete analysis is composed by a CFD model and its experimental validation. The experimental results fits with CFD model results. Thermal performance shows promising results compared to the state of the art. Next steps in the receiver development will be its upscaling. Abstract: A new active, first of its kind, volumetric receiver prototype is used in this study to obtain the conclusions about its thermal performance. The rotating disks cooling, was studied first, numerically, using a CFD software and second, experimentally, using a laboratory-scale prototype. This study evaluates the convective heat transfer from rotating disks to a transverse air crossflow. The thermal energy exchange on the disk surfaces allows us to calculate the heat transfer coefficient from disk surface temperature and the thermal performance of the receiver prototype and local Nusselt number through the receiver depth are also a key point in the research. The influence of rotational speed and air mass flow on the heat transfer coefficient is also studied. Differences between numerical and experimental results show high concordance, with a relative error below 15% in the worst point. The thermal performance shown by the lab-scale receiver is promising for the further development of the active Open Volumetric Air Receivers (OVAR) technology. The obtained thermal efficiency results show an improvement of around 10% at 900 °C when compared to the current state of the art of volumetric receivers.